Making sense of sound: Visceral sonic mapping as a research tool. (August 2016) - Duffy, Michelle; Waitt, Gordon; Harada, Theresa
Abstract: This paper offers a contribution to ongoing discussions of the role of sound for producing geographical knowledge. It is argued that sound is an inherent component of critical research of emotions, society and space. Yet we note that there is a lack of practical advice as to how this might come about. In this paper we offer a methodological approach for the analysis of sound that we term visceral sonic mapping to help critical geographers progress enlivening geography through recent rethinking of 'the body'. First, we provide a progress report to chart theoretical and methodological approaches to sound within geography and cognate disciplines. We then sketch a theoretical understanding of the visceral and our visceral sonic mapping. To demonstrate how this method might be productively put to use we draw on empirical material from a driving ethnography that was undertaken in a regional Australian centre from 2010 to 2011.